Alphaworld: a present for our teacher - Luk, Patrick (Oxford University Press Melbourne, 2004)
"A Present for Our Teacher" is a heartwarming story that centers on a group of students who want to express their appreciation for their teacher. As they brainstorm ideas for the perfect gift, the narrative highlights their teamwork, creativity, and the special bond they share with their teacher. Throughout their planning, the students reflect on the lessons they've learned and the impact their teacher has had on their lives. The story emphasizes themes of gratitude, friendship, and the importance of recognizing those who inspire and guide us. In the end, the thoughtful gift symbolizes their affection and respect, celebrating the meaningful connections in a classroom setting.